Creating Real Estate Maps by Using GIS: A Case Study of Atakum-Samsun/Turkey - Ahmet Sesli, F.A. (Technical University of Kosice Letna 9 Kosice 04200, 2015)
Determining the real estate evaluations and reflecting them on taxations are among the most important economic resources of the developed countries. In Turkey, the system is not able to ground the real estate evaluations on scientific criteria yet, which causes various problems in applications regarding real estate evaluations (such as estate tax, expropriation, court surveillances) and an important economic loss. Thus, it is required to generate tax-base real estate evaluation maps within the scope of the legal legislation in Turkey. This study is aimed to generate a fast, up-to-date and dynamic evaluation map that would form a base for the real estate taxation. The closeness of real estates to the technical infrastructure and social equipment areas and their variety affect the real estate evaluations either positively or negatively and form the local benefit for real estates. This study determined the areas (such as main roads, green spaces, trading areas and urban attraction centers) affecting the evaluations of real estates depending on their positions. In order to make position-based decisions about the data being stored in the Geographical Information System, the geographical data were questioned and monitored by analyzes. The acquired data were exposed to necessary analyzes in the relevant modules of the GIS programs, which enabled us to grade the factors affecting the evaluation for each parcel and try to generate real estate evaluation maps depending on the evaluation-effect factors to be selected as dynamics. Parcel-based real estate evaluations were determined by imposing vector-based cadastral maps on these maps being generated. In this study, a raster real estate evaluation map was generated in unstructured parcels of a sample neighborhood via the scoring method and with the help of the Multi-Criteria Decision-Making Analysis and both environmental and social factors. This system enabled us to question and analyze the features of parcels and thus rapidly change them according to the system variables. © 2015 Technical University of Kosice. All rights reserved.
Keywords: Geographical Information Systems (GIS); Land Valuation; Multi-Criteria Decision Making Analysis; Real Estate Evaluation Maps